American Pantheon: Poems. - Mock, Jeff (2005)
Keywords: dept.eng; faculty_collection; sabbatical_report

Conscience and Purpose: Fiction and Social Consciousness in Howells, Jewett, Chesnutt, and Cather - Petrie, Paul R. (Studies in American literary realism and naturalism, 2005)
"In a series of influential essays that appeared in Harper's, W.D. Howells argued for literature as a vehicle for social change. Literature could and should, Howells suggested, mediate across divisions of class and region, fostering cross-cultural sympathies that would lead to comprehensive social and ethical reform." "Paul R. Petrie explores the legacy of Howells's beliefs as they manifest themselves in his fiction and in the works of three major American writers - Charles W. Chesnutt, Sarah Orne Jewett, and Willa Cather. Each author struggled to adapt Howells's social-ethical agenda for literature to his or her own aesthetic goals and to alternative conceptions of literary purpose. Jewett not only embraced Howell's sense of social mission but also extended it by documenting commonplace cultural realities in a language and vision that was spiritual and transcendent. Chesnutt sought to improve relations between Anglo readers and African Americans, but his work, such as The Conjure Woman, also questions literature's ability to repair those divides." "Finally, Petrie shows how Cather, as she shifted from journalism to fiction writing, freed herself from Howells's influence. Alexander's Bridge (1912) and O Pioneers! (1913) both make reference to social and material realities but only as groundwork for character portrayals that are mythic and heroic. The result of Petrie's exploration is a refreshing reassessment of Howell's legacy and its impact on American literature and social history at the turn of the century."--Jacket.
Keywords: Chesnutt, Charles W. (Charles Waddell), 1858-1932; Ethics; American fiction; Ethics; Cather, Willa, 1873-1947; Ethics; Howells, William Dean, 1837-1920; Ethics; Jewett, Sarah Orne, 1849-1909; History and criticism; Ethics in literature; Literature and society; SCSU Faculty Scholar Award; United States; Social ethics in literature; Conscience in literature; award_winner; dept.eng; faculty_collection

Laws of My Nature: Poems - Schilpp, Margot (Carnegie Mellon poetry, 2005)
Keywords: American poetry; dept.eng; faculty_collection

Hardboot: Poems New & Old - Shipley, Vivian (Louisiana Literature Press, Southeastern Louisiana University, 2005)
Keywords: Poets, American; dept.eng; faculty_collection

Caduceus: Poets at Art Place V.3 - Shipley, Vivian; Fusco, Tony; Yale University School of Medicine Yale Medical Group Art Place; Yale Medical Group (Yale Medical Group Art Place, 2005)
Poetry included in the partial contents note is composed of contributions from the faculty, staff, students and alumni of Southern Connecticut State University.
Keywords: Connecticut; Literature and science; New Haven; Literature and science; Poetry; Poetry; United States; United States; New Haven (Conn.); dept.eng; faculty_collection

No Angels but These - Sonnenschein, Dana (Main Street Rag's editor's choice chapbook series, 2005)
Keywords: dept.eng; faculty_collection

Charles Brockden Brown's Ormond, property exchange, and the literary marketplace in the early American republic - Ellis, S. (Studies in the Novel, 2005)
Keywords: dept.eng; ⛔ No DOI found

The paper bag principle: Of the myth and the motion of colorism - Kerr, A.E. (Journal of American Folklore, 2005)
This article, extracted from a larger study, is attentive to the national folk culture of African-American communities - especially rumor and legend - in a number of city centers. The study begins with Washington, D.C., as a representative model to examine the role of complexion-related lore in black neighborhoods, organizations, and institutions, and then extends outward to other urban areas. Complexion lore, the article argues, functioned as a sophisticated negotiation of racism, wherein black residents complicated American urban principles of inclusion and exclusion by integrating color notions into institutional oral history. Copyright © 2005 by the Board of Trustees of the University of Illinois.
Keywords: dept.eng; dept.wgs

The economics of authorship: Online paper mills, student writers, and first-year composition - Ritter, K. (College Composition and Communication, 2005)
Using sample student analyses of online paper mill Web sites, student survey responses, and existing scholarship on plagiarism, authorship, and intellectual property, this article examines how the consumerist rhetoric of the online paper mills construes academic writing as a commodity for sale, and why such rhetoric appeals to students in first-year composition, whose cultural disconnect from the academic system of authorship increasingly leads them to patronize these sites.
Keywords: dept.eng; ⛔ No DOI found